Upaya Peningkatan Aktivitas Pembelajaran Tematik Delapan Daerah Tempat Tinggalku melalui PPjBL Kelas IV Sekolah Dasar - Wibowo, Dwy Unggul; Wardani, Naniek Sulistya; Kukuh, Aris (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
This study aims to (1) determine whether the increase in learning activities in thematic learning 8 areas where I live can be sought through PPjBL fourth-grade elementary school students; (2) find out how the increase in learning outcomes in thematic learning 8 areas where I live can be sought PPjBL fourth grade elementary school students. This class action research (PTK) uses the spiral model, proposed by Kemmis and McTaggart. the research model uses a minimum Each of the two cycles consists of three phases: planning, implementation, observation, and reflection. The subjects were students of Class IV SDN 02 Plosoharjo as many as 25. Data collection techniques in research include observation and documentation. Observation in this study was conducted to observe the activities of students using the PPjBL learning model. Based on the results of the analysis of the activeness of pre-cycle students into the category of very active as many as 2 students (8%), students who fall into the category of action as many as 8 students (32%) students who fall into the category of moderately active as many as 9 (36%). Students who fall into the category of less active as much as 6 (24%). In the first cycle of students into the category of very active as many as 3 students 12%, students who fall into the category of action as many as 7 students (28%) Students who fall into the category of students up to the age of 11 who are quite active (44%). Four students fall into the less active category. (16%). The increase occurred in the second cycle with students in the very active category as many as 6 students (24%), students who fall into the category of action as many as 10 students (40%) students who fall into the category of sufficient there are 7 students (28%) and less active Category 2 students (8%) thus it has been proven that the learning model PPjBL can increase.